Challenges of endoscopic retrograde cholangiopancreatography in patients with Billroth II gastrointestinal anatomy: A review article. Issue 12 (24th November 2019) - Pribadi, Rabbinu Rangga; Rani, Abdul Aziz; Abdullah, Murdani
Abstract : Endoscopic retrograde cholangiopancreatography (ERCP) is a combination of endoscopy and fluoroscopy that is commonly used in the management of pancreatobiliary diseases. ERCP can be challenging if performed in surgically altered anatomy, such as a Billroth II reconstruction, compared with native anatomy and usually has a lower success rate. We identified five emerging challenges in such patients. These are the choice of endoscope, the identification of afferent loop, reaching the duodenal stump, cannulation in the reverse position, and endoscopic sphincterotomy. Performing ERCP in patients with a Billroth II reconstruction needs adequate knowledge, proper skill, and experience to achieve a good clinical outcome.